Analisis Penerapan Teknologi Informasi dalam Pemasaran Digital pada UMKM di Tanjung Sebauk : Dampak terhadap Peningkatan Daya Saing dan Inovasi Produk - Afrija Khoirun Nissa; Aulia Firda Rahmadani; Ayattullah Muhaddis Azim; Bayu Setiawan; Hamidah Hamidah; Jelica Rosyiana Silalahi; Lia Safitriani; Muhammad Rangga Pranama Putra; Resa Ristalia; Yohani Natalia Simanulang (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
This study aims to analyze the application of information technology in digital marketing in Micro, Small, and Medium Enterprises (MSMEs) in Tanjung Sebauk. The background of this study is based on the fact that although local MSMEs have begun to utilize social media and digital technology, their use is still limited to the basic level and is not yet optimal. This research also uses a qualitative method with a descriptive phenomenological approach, through interviews, observation, and documentation of MSME actors in the region. The results of this study show that social media such as WhatsApp and Instagram have indeed been used as promotional tools, but have not been utilized strategically. The adoption rate of e-commerce is also still very low, with only a small number of MSME actors trying to market their products through online platforms. In addition, the digital marketing strategies implemented are still reactive, unplanned, and lack consistency in building brand image. In this case, it can be concluded that MSMEs in Tanjung Sebauk have great potential to grow through the use of digital technology, but they still need to improve their digital literacy, receive ongoing assistance, and develop more structured marketing plans in order to compete in a wider market and, of course, become better known to the outside community.